Malignant Melanoma in A Rectal Polyp - Shah, Amar; Chaudhari, Sanjay; Shah, Apurva (National Journal of Community Medicine, 2012)
Malignant melanoma is very rare in the rectum. Prompt diagnosis and treatment is necessary as chances of metastasis is very high. A 56 year old male patient came to surgical OPD for complaint of something coming out per rectum. Polyp was identified on per rectal examination the biopsy revealed malignant melanoma. Abdominoperineal resection was done. We reported this case as it is uncommon and also there is controversy in surgical treatment of choice.